A medical device-grade T1 and ECV phantom for global T1 mapping quality assurance—the T1 Mapping and ECV Standardization in cardiovascular magnetic resonance (T1MES) program. Issue 1 (December 2016) - Captur, Gabriella; Gatehouse, Peter; Keenan, Kathryn; Heslinga, Friso; Bruehl, Ruediger; Prothmann, Marcel; Graves, Martin; Eames, Richard; Torlasco, Camilla; Benedetti, Giulia; Donovan, Jacqueline; Ittermann, Bernd; et al.
Abstract Background T1 mapping and extracellular volume (ECV) have the potential to guide patient care and serve as surrogate end-points in clinical trials, but measurements differ between cardiovascular magnetic resonance (CMR) scanners and pulse sequences. To help deliver T1 mapping to global clinical care, we developed a phantom-based quality assurance (QA) system for verification of measurement stability over time at individual sites, with further aims of generalization of results across sites, vendor systems, software versions and imaging sequences. We thus created T1MES: The T1 Mapping and ECV Standardization Program. Methods A design collaboration consisting of a specialist MRI small-medium enterprise, clinicians, physicists and national metrology institutes was formed. A phantom was designed covering clinically relevant ranges of T1 and T2 in blood and myocardium, pre and post-contrast, for 1.5 T and 3 T. Reproducible mass manufacture was established. The device received regulatory clearance by the Food and Drug Administration (FDA) and Conformité Européene (CE) marking. Results The T1MES phantom is an agarose gel-based phantom using nickel chloride as the paramagnetic relaxation modifier. It was reproducibly specified and mass-produced with a rigorously repeatable process. Each phantom contains nine differently-doped agarose gel tubes embedded in a gel/beads matrix. Phantoms were free of air bubbles and susceptibility artifacts at both field strengths and T1 maps were free from off-resonance artifacts. The incorporation of high-density polyethylene beads in the main gel fill was effective at flattening theB 1 field. T1 and T2 values measured in T1MES showed coefficients of variation of 1 % or less between repeat scans indicating good short-term reproducibility. Temperature dependency experiments confirmed that over the range 15–30 °C the short-T1 tubes were more stable with temperature than the long-T1 tubes. A batch of 69 phantoms was mass-produced with random sampling of ten of these showing coefficients of variations for T1 of 0.64 ± 0.45 % and 0.49 ± 0.34 % at 1.5 T and 3 T respectively. Conclusion The T1MES program has developed a T1 mapping phantom to CE/FDA manufacturing standards. An initial 69 phantoms with a multi-vendor user manual are now being scanned fortnightly in centers worldwide. Future results will explore T1 mapping sequences, platform performance, stability and the potential for standardization.